The Effect of Product Quality, Price and Promotion on Purchasing Decisions - Saepuloh, Asep; Hisani, Doris Roif (INNOVATION RESEARCH JOURNAL, 2020)
Currently in the mobile phone business going on a very tight competition, any company or operator of a mobile card issuing competing to create various alternatif option to influence purchasing decisions and win the competition. This study aims to test the effect of product quality, price, and promotion on purchasing decisions. The number of samples in this study were 100 Gresik Telkomsel consumers. Analysis of the data used is multiple linear regression analysis. The results of this study concluded that the results of simultaneous testing of product quality, price, and promotion of purchasing decisions. The results of partial testing of product quality have a significant effect on purchasing decisions, prices have a significant effect on purchasing decisions, and promotions have a significant effect on purchasing decisions.